The Effective Commands Used By The Teacher During English Teaching in Managing Students with Disruptive Behavior - Dewi, Anak Agung Nareswari Tungga; Utami, Ida Ayu Made Istri; Wahyuni, Luh Gede Eka (Universitas Pendidikan Ganesha, 2022)
Commands are a crucial tool for classroom management used by the teacher to direct the students to start and end the activities. This qualitative descriptive research was aimed at identify types of students’ disruptive behavior that found at SD Lab Undiksha Singaraja especially in fifth grade, identify types of effective commands are given by an English teacher and analyze how the effective commands are given to students with disruptive behavior. This study was a case study research. The data were collected through observation, questionnaire, and interview. The result of this study showed that students ‘disruptive behavior at SD Lab Undiksha Singaraja classified as The Immature category such as talking with their friend, paying no attention to the teacher and lesson, walking around the class, and making a noise. To overcome students’ disruptive behavior, the teacher was used several types of commands. There were five types of Effective command such as Interrogation command, Don’t command, Indirect command, Regular command and Other command. Those commands were effective commands because there was compliance and response from the students.